Lean thinking in the highways construction sector: motivation, implementation and barriers. Issue 3 (17th February 2018) - Tezel, Algan; Koskela, Lauri; Aziz, Zeeshan
Abstract: The interest in lean thinking in the UK's civil construction industry is on the rise. The research presented in the paper evaluates the adoption of lean thinking in the highways construction sector by investigating 7 motivation factors, 20 lean techniques and 16 barriers through in-depth interviews with 20 sector managers and a questionnaire survey of 110 responses. The findings show the existence of strong external motivational factors for lean thinking such as clients' push and companies' expectation of winning more contracts alongside lean's operational benefits. Limited adoptions of the lean techniques, mostly in the stepwise process improvement cycle, the Last Planner System and Visual Management, were determined. This raises concerns about 'pseudo-lean' practices in the sector. Lack of standardisation, insufficient benefit capturing, insufficient know-how, insufficient control of the entire value stream and limited view to the techniques were found as the top barriers.